Clinical value of radionuclide oesophageal transit measurement. Issue 6 (June 1986) - de Caestecker, J S; Blackwell, J N; Adam, R D; Hannan, W J; Brown, J; Heading, R C
Abstract : We have reviewed our experience of 150 patients to assess the clinical value of radionuclide oesophageal transit measurements in relation to established oesophageal motility investigations. Achalasia and conditions characterised by incoordinate oesophageal motor activity were detected with equal frequency by manometry and radionuclide transit measurement. Radionuclide transit measurements identified abnormalities not detected by manometry in 18 patients, and manometry was abnormal in 26 patients with normal radionuclide studies, including all patients with nutcracker oesophagus and most with hypertensive lower oesophageal sphincter. The overall sensitivity of radionuclide transit measurements in detecting oesophageal dysmotility was 75%, the sensitivity of manometry was 83% and that of conventional barium radiology 30%. We conclude that radionuclide transit measurement is a useful test for patients with suspected oesophageal motility disorders. Although it has limitations as a screening test, it provides additional information which complements oesophageal manometry.